Volume 3C: General 1993
DOI: 10.1115/93-gt-430
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Steady and Unsteady Relative Flow in a Model Centrifugal Impeller Passage

Abstract: The behaviour of the relative flow in centrifugal turbomachines is extremely complex due to the existence of various fluid dynamic phenomena and their interaction. At design and off-design operating conditions, the relative flow is subject to stationary unsteadiness which includes flow separation and wakes associated with passage pressure gradients, secondary flows, and boundary layer stability. It may also be subject to periodic unsteadiness such as is the rotating stall and cyclic flow phenomena induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…At an overload flow rate of 1.2 Q BEP , the streamlines follow the blade curvature without flow separation, and a low-velocity region develops at the blade outlet. is occurrence has been previously reported [32,33]. e distribution of velocity is uniform at the outlet of the impeller and has minimal effects on the slip factor.…”
Section: Influence Of Flow Rate On Slip Factorsupporting
confidence: 62%
“…At an overload flow rate of 1.2 Q BEP , the streamlines follow the blade curvature without flow separation, and a low-velocity region develops at the blade outlet. is occurrence has been previously reported [32,33]. e distribution of velocity is uniform at the outlet of the impeller and has minimal effects on the slip factor.…”
Section: Influence Of Flow Rate On Slip Factorsupporting
confidence: 62%
“…The smooth and blade curvature congruent flow within the blade passages can changed to a stalled flow as reported by Pedersen et al [8] or becomes a significant flow separation as experimentally observed by Liu et al [9] and Abramian and Howard [10]. Other measurements done by Wuibaut et al [11], Westra et al [12], Visser [13], Choi et al [14] further demonstrated that flow field within impeller passages is highly complex and depends on flow rate, number of blades, blade curvature and specific speed as well.…”
Section: Introductionmentioning
confidence: 60%
“…Due to decrease of flow rate, radial flow decelerated on shroud/suction surface, the secondary flow and vorticity increases in the passage. Further investigation by Abramian and Howard [10] using laser Doppler anemometer measurement showed that pressure side mean flow separation under low flow condition within the impeller passage is affected by a combined effect between a secondary vorticity initiated at the inlet and a potential vortex which dominates the flow at impeller exit. The flow within the passage of the highly backward swept blades also dominated by the rotational effect because of the changing Rossby number along the curvature of the blade from the leading edge to trailing edge.…”
Section: Introductionmentioning
confidence: 99%